Design and test of two-wheeled walking hemp harvester - Huang, Jicheng; Shen, Cheng; Ji, Aimin; Tian, Kunpeng; Zhang, Bin; Li, Xianwang; Chen, Qiaomin (International Journal of Agricultural and Biological Engineering, 2020)
Aiming at the planting characteristics of hemp in southern hilly regions, a two-wheeled walking hemp harvester suitable for harvesting hemp in southern hilly regions is studied and designed. The harvester mainly consists of a header frame, single-moving cutter, cutter mechanical transmission, stalk lifter and reel, stalk divider, stalk horizontal conveyor, wheeled chassis, motor, gearbox, etc. To improve the cutting performance of the two-wheeled walking hemp harvester, response surface tests of three levels are conducted for three factors influencing the operation quality, including the cutting speed, blade length, and forward speed, on the constructed hemp cutting test bench. Moreover, test results are analyzed with the response surface method, and multi-objective optimization is carried out for the regression mathematical model with Design-Expert software. Results show that when the cutting speed is 1.2 m/s, the blade length is 120 mm, forward speed is 0.6 m/s, the cutting efficiency is 38.92 stalks/s, the cutting power is 776.37 W and the failure rate is 6.24%. Trial production of sample machine and field trial are finished according to the optimized parameters and structural design scheme, and the test results reveal that the cutting rate can reach 92.5%, the rate of transmission can reach 86.7%, the productivity is 0.18 hm2/h, and all performance indexes can meet the design requirements. This research can provide references for resolving the mechanical harvesting of hemp. Keywords: hemp, harvester, structural design, parameter optimization, productivity DOI: 10.25165/j.ijabe.20201301.5223 Citation: Huang J C, Shen C, Ji A M, Tian K P, Zhang B, Li X W, et al. Design and test of two-wheeled walking hemp harvester. Int J Agric & Biol Eng, 2020; 13(1): 127–137.